Vortex Shedding Lock-In due to Pitching Oscillation of a Wind Turbine Blade Section at High Angles of Attack - Craig Meskell; Alberto Pellegrino (International Journal of Aerospace Engineering)
The unsteady flow around a pitching two-dimensional airfoil section (NREL S809) has been simulated using unsteady RANS with the transition SST turbulence model. This geometry is chosen to represent a wind turbine blade in a standstill configuration. The Reynolds number is Re=106 based on a chord length of 1 m. A prescribed sinusoidal pitching motion has been applied at a fixed amplitude of 7° for a range of high angles of attack 30°<α<150°. At these incidences, the airfoil will behave more like a bluff body and may experience periodic vortex shedding. It is well known that, in bluff body flows, oscillations can lead to a lock-in (lock-in) of the vortex shedding frequency, fv, with the body’s motion frequency, fp. In order to investigate the susceptibility of airfoil to lock-in, the frequency ratio r (r=fp/fv0) has been varied around r=1. The lock-in region boundaries have been proposed, and an analysis of the effect of the oscillation amplitude has been conducted. The lock-in map obtained suggests that, for the vibration amplitude considered, the risk of vortex-induced vibration is more significant in the regions of α≈40° and α≈140°, i.e., for shallower characteristic lengths. Finally, a lumped parameter wake oscillator model has been proposed for pitching airfoils. This simple model is in qualitative agreement with the CFD results.